Speech delivered by Dr. Salvador Allende, President of the Republic of Chile before The General Assembly of The United Nations, December 4, 1972. - Embassy of Chile (Washington, DC US: Embassy of Chile, 1972)
Reproduce el discurso pronunciado por el Presidente de la República de Chile, Dr. Salvador Allende, con motivo de la Asamblea General de las Naciones Unidas del 4 de diciembre de 1972.
Keywords: CHILE; ONU; ALLENDE, SALVADOR; DISCURSOS